Two novel fluorescent immunoassays for multianalyte detection - Murphy, Brian M., author; Henry, Charles S., advisor (Colorado State University. Libraries, 2009)
Since their inception several decades ago, immunoassays have become the workhorse technology for measuring both proteins and small molecules in complex biological matrices. Immunoassay technologies have become important tools in the field of medicine, where measurement of a variety of analytes in media such as urine, blood, or serum is essential. To diagnose many diseases and conditions, clinicians rely on the quantification of several biomarkers in a sample. However, common immunoassay systems such as ELISA can measure only a single analyte at a time, and can take hours to complete. This dissertation details two new immunoassay methods designed to simultaneously quantify several analytes from a single sample, Protein patterning on a silicon nitride wafer is performed for a micromosaic fluorescent immunoassay in which the thyroid hormone thyroxine (T4), inflammation biomarker CRP, and BSA-conjugated 3-nitrotyrosine (3NT) are assayed in the competitive format. The assay for 3NT is then combined with a sandwich immunoassay for superoxide hi dismutase (SOD) and catalase (CAT), demonstrating that micromosaic immunoassays can be used to simultaneously quantitate small and large targets. In a second approach, a unique capillary electorphoresis immunoassay is performed for 3NT, carboxy-methyl lysine (CML), and thyroxine (T4). Termed a cleavable tag immunoassay (CTI), the method relies on bioconjugation of IgGs to unique chemically cleavable fluorophores which serve as reporter groups for each analyte. A novel method for bioconjugation of IgG to fluorophore to produce the conjugates is presented. Microchip CE with fluorescence detection is demonstrated and resolution is optimized for the separation of three different CTI conjugate fragments. This dissertation will argue for the viability of both methods as relevant in the development of true multianalyte clinical diagnosis assays.
Keywords: fluorescence; immunoassays; multianalyte; analytical chemistry